Evaluating Long-term Outcomes of NHS Stop Smoking Services (ELONS): a prospective cohort study. - Dobbie, Fiona (Health Technol Assess, 2015)
BACKGROUND: NHS Stop Smoking Services (SSSs) provide free at the point of use treatment for smokers who would like to stop. Since their inception in 1999 they have evolved to offer a variety of support options. Given the changes that have happened in the provision of services and the ongoing need for evidence on effectiveness, the Evaluating Long-term Outcomes for NHS Stop Smoking Services (ELONS) study was commissioned. OBJECTIVES: The main aim of the study was to explore the factors that determine longer-term abstinence from smoking following intervention by SSSs. There were also a number of additional objectives. DESIGN: The ELONS study was an observational study with two main stages: secondary analysis of routine data collected by SSSs and a prospective cohort study of service clients. The prospective study had additional elements on client satisfaction, well-being and longer-term nicotine replacement therapy (NRT) use. SETTING: The setting for the study was SSSs in England. For the secondary analysis, routine data from 49 services were obtained. For the prospective study and its added elements, nine services were involved. The target population was clients of these services. PARTICIPANTS: There were 202,804 cases included in secondary analysis and 3075 in the prospective study. INTERVENTIONS: A combination of behavioural support and stop smoking medication delivered by SSS practitioners. MAIN OUTCOME MEASURES: Abstinence from smoking at 4 and 52 weeks after setting a quit date, validated by a carbon monoxide (CO) breath test. RESULTS: Just over 4 in 10 smokers (41%) recruited to the prospective study were biochemically validated as abstinent from smoking at 4 weeks (which was broadly comparable with findings from the secondary analysis of routine service data, where self-reported 4-week quit rates were 48%, falling to 34% when biochemical validation had occurred). At the 1-year follow-up, 8% of prospective study clients were CO validated as abstinent from smoking. Clients who received specialist one-to-one behavioural support were twice as likely to have remained abstinent than those who were seen by a general practitioner (GP) practice and pharmacy providers [odds ratio (OR) 2.3, 95% confidence interval (CI) 1.2 to 4.6]. Clients who received group behavioural support (either closed or rolling groups) were three times more likely to stop smoking than those who were seen by a GP practice or pharmacy providers (OR 3.4, 95% CI 1.7 to 6.7). Satisfaction with services was high and well-being at baseline was found to be a predictor of abstinence from smoking at longer-term follow-up. Continued use of NRT at 1 year was rare, but no evidence of harm from longer-term use was identified from the data collected. CONCLUSIONS: Stop Smoking Services in England are effective in helping smokers to move away from tobacco use. Using the 52-week CO-validated quit rate of 8% found in this study, we estimate that in the year 2012-13 the services supported 36,249 clients to become non-smokers for the remainder of their lives. This is a substantial figure and provides one indicator of the ongoing value of the treatment that the services provide. The study raises a number of issues for future research including (1) examining the role of electronic cigarettes (e-cigarettes) in smoking cessation for service clients [this study did not look at e-cigarette use (except briefly in the longer-term NRT study) but this is a priority for future studies]; (2) more detailed comparisons of rolling groups with other forms of behavioural support; (3) further exploration of the role of practitioner knowledge, skills and use of effective behaviour change techniques in supporting service clients to stop smoking; (4) surveillance of the impact of structural and funding changes on the future development and sustainability of SSSs; and (5) more detailed analysis of well-being over time between those who successfully stop smoking and those who relapse. Further research on longer-term use of non-combustible nicotine products that measures a wider array of biomarkers of smoking-related harm such as lung function tests or carcinogen metabolites. FUNDING: The National Institute for Health Research Health Technology Assessment programme. The UK Centre for Tobacco and Alcohol Studies provided funding for the longer-term NRT study.